The two isoforms of the cAMP-dependent protein kinase catalytic subunit are involved in the control of dimorphism in the human fungal pathogen Candida albicans - Cloutier, Monikca (2003)
We have cloned the Candida albicans TPK2 gene encoding a cAMP-dependent protein kinase (PKA) catalytic subunit and generated a tpk2 homozygous null mutant to assess its ability to germinate in liquid media. N-acetylglucosamine (GlcNAc)-induced germ-tube formation was attenuated in the tpk2 strain and enhanced by compounds that are known to increase the PKA activity in situ. Germination was completely blocked in the presence of the myristoylated derivative of the heat-stable PKA inhibitor (MyrPKI). These results indicate that TPK1 acts positively in regulating the morphogenetic transition in C. albicans in the absence of the TPK2 gene. We were able to identify an mRNA from this second form of PKA in both wild-type and tpk2 null mutant cells. We found that PKA activity measured in the mutant lacking the TPK2 gene was about 10% of that displayed by the wild-type. The finding that the germinative response of tpk2 null mutant to serum was severely diminished at low serum concentrations indicates that the level of PKA is an important determinant of filamentous growth at low serum concentrations. The extent of germination attained at higher serum concentrations (5%) was similar in the wild-type and in the tpk2 null mutant strains suggesting that under these conditions germination was triggered through a PKA-independent pathway.